Physical and Chemical Properties of Soil in Vegetable Fields After Compost Application - Suwandi Said; Mohammad Ikbal Bahua; Nurmi, Nurmi (International Journal of Technology and Education Research, 2025)
The degradation of soil physical and chemical properties in intensive vegetable cultivation systems necessitates effective and sustainable amelioration strategies. This study aimed to examine the effect of compost dosage on soil Bulk Density, nitrogen, phosphorus, and potassium in vegetable land. The study employed a Randomized Block Design (RBD) with three compost dosage treatments (P0 = 0 ton ha⁻¹, P1 = 15 ton ha⁻¹, P2 = 30 ton ha⁻¹) and three replications. The measured parameters included Bulk Density (BD), total nitrogen (N), available phosphorus (P), and exchangeable potassium (K). Data were analyzed using ANOVA followed by Duncan's Multiple Range Test (DMRT) at the 5% significance level. Results indicated that compost application significantly affected all tested parameters. Bulk Density decreased significantly from 1.44 g cm⁻³ (P0) to 1.28 g cm⁻³ (P2). Total nitrogen increased from 0.15% (P0) to 0.21% (P2). Available phosphorus increased very significantly from 7.71 ppm (P0) to 11.53 ppm (P2), while exchangeable potassium increased from 0.13 cmol kg⁻¹ (P0) to 0.29 cmol kg⁻¹ (P2). The P2 treatment (30 ton ha⁻¹) was the most effective dosage for restoring soil physical and chemical quality in intensive horticultural systems.